2022
DOI: 10.7759/cureus.33104
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Intradialytic Hypertension Using Kidney Disease: Improving Global Outcomes (KDIGO) Suggested Definition in a Single Hemodialysis Centre in Pakistan

Abstract: Objectives: To estimate the frequency of intradialytic hypertension (IDH) in our centre as per the definition suggested by Kidney Disease: Improving Global Outcomes (KDIGO).Methods: A cross-sectional study was conducted at the dialysis department of The Kidney Centre Post Graduate Training Institute (PGTI) Karachi, Pakistan from August 2021 to October 2021 among 263 endstage kidney disease (ESKD) patients on maintenance hemodialysis (MHD) aged ≥ 18 years of both genders. The study outcome was the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These medications promote diuresis and help maintain fluid balance and hemodynamic stability in this vulnerable population. 14,18,19 The low utilization of ACE inhibitors in this study may be attributed to individual patient characteristics, contraindications, or specific preferences of healthcare providers. Similarly, thiazide diuretics are often used as add-on therapy to manage hypertension in CKD patients.…”
Section: Discussionmentioning
confidence: 96%
“…These medications promote diuresis and help maintain fluid balance and hemodynamic stability in this vulnerable population. 14,18,19 The low utilization of ACE inhibitors in this study may be attributed to individual patient characteristics, contraindications, or specific preferences of healthcare providers. Similarly, thiazide diuretics are often used as add-on therapy to manage hypertension in CKD patients.…”
Section: Discussionmentioning
confidence: 96%
“…IDHYPER represents a frequent finding among patients on regular HD, with several research efforts being conducted in this field, as shown in Table 1. According to a recent study conducted in a single HD center in Pakistan, the prevalence of IDHYPER was 16% using the KDIGO IDHYPER definition, and this finding was more common in the elderly and those on antihypertensive medication [20]. A lower rate of IDHYPER (5% of sessions) was found in a cohort of HD patients in Eritrea [21].…”
Section: Epidemiology Of Idhyper and Associated Risk Factorsmentioning
confidence: 99%